2010
DOI: 10.1155/2010/823210
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Calciphylaxis Associated with Primary Hyperparathyroidism: A Case Report and Review of the Literature

Abstract: Calciphylaxis, or calcific uremic arteriolopathy, commonly affects people with end-stage renal disease and carries with it a high rate of morbidity and mortality. Here, we present the unusual case of a 56-year-old woman, with extensive medical problems, who developed calciphylaxis in the presence of primary hyperparathyroidism. Our patient initially presented with bilateral, exquisitely tender thigh lesions. The diagnosis of calciphylaxis was rendered histologically by extensive calcification of the subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, syndromes resembling calciphylaxis have been reported in individuals with pre-end-stage renal disease-staged CKD and even more rarely in those without any evidence of renal dysfunction but with inflammatory bowel disease, malignancy, trauma, and primary hyperparathyroidism. [4][5][6][7] This disease entity is characterized by calcification, intimal hypertrophy, and thrombosis of small vessels that slowly lead to tissue ischemia followed by infarction. Predominantly affecting subcutaneous tissue, this microvasculopathic process leads to the formation of painful nodules or plaques, which are often described as erythematous or violaceous foci that later erupt as necrotizing, nonhealing ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, syndromes resembling calciphylaxis have been reported in individuals with pre-end-stage renal disease-staged CKD and even more rarely in those without any evidence of renal dysfunction but with inflammatory bowel disease, malignancy, trauma, and primary hyperparathyroidism. [4][5][6][7] This disease entity is characterized by calcification, intimal hypertrophy, and thrombosis of small vessels that slowly lead to tissue ischemia followed by infarction. Predominantly affecting subcutaneous tissue, this microvasculopathic process leads to the formation of painful nodules or plaques, which are often described as erythematous or violaceous foci that later erupt as necrotizing, nonhealing ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 Several strategies aimed at treating and preventing this affliction in the nondialysis population have been reported in the literature. These include early parathyroidectomy, 5,7 sodium thiosulfate, 8,9 vitamin D analogs, 9 bisphosphonates, 10 cinacalcet, 10,11 and hyperbaric oxygen. 12 Unfortunately, none of these maneuvers have been shown to be universally beneficial and the outcome for most patients afflicted with calciphylaxis remains quite poor.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no studies demonstrating the optimal duration of intensified dialysis, I strongly recommend a course of dialysis 5-7 days per week for the first couple weeks of treatment, with the duration of this intensified dialysis therapy depending on clinical response. The relationship of calciphylaxis with hyperparathyroidism is best seen in nonuremic patients (4,14,21,42). There are reports that parathyroidectomy may benefit wound healing (43)(44)(45) and increase survival (5,39,45), whereas other studies demonstrated no benefit to parathyroidectomy (4,46).…”
Section: Managementmentioning
confidence: 99%
“…In fact, Budisavljevic and colleagues reviewed 47 patients with CUA, 31of whom underwent parathyroidectomy; 50% of these patients died within 9 weeks of surgery (47). Thus, the role of parathyroidectomy remains controversial (5,8,42,(48)(49)(50). Parathyroidectomy is unlikely to be useful when PTH concentrations are not markedly elevated (1,5,41).…”
Section: Managementmentioning
confidence: 99%
“…3 To the best of knowledge, an around 25 case of calciphylaxis due to primary hyperparathyroidism has been reported so far in world literature. [4][5] This case had the most extensive presentation of calciphylaxis reported till date. Hence, report this case for its rarity as well as for highlighting its unusual presentation to contribute in part to the better understanding and awareness of this condition.…”
Section: Introductionmentioning
confidence: 99%